A Clinical Investigation on Serum Amyloid A Concentration in Client-Owned Healthy and Diseased Cats in a Primary Care Animal Hospital - Masashi Yuki; Reina Aoyama; Masahiro Nakagawa; Takashi Hirano; Eiji Naitoh; Daiki Kainuma (Veterinary Sciences, 2020)
Although measurement of serum amyloid A (SAA) concentration in client-owned cats has already been shown to be clinically useful, limited data are available on common diseases at primary care hospitals. In this study, we measured the SAA concentration in cats with various diseases and investigated their clinical significance using a primary care hospital as a population. We measured the SAA concentrations in healthy cats (n = 98) and those with various clinical signs (n = 444). The SAA concentrations in healthy cats did not differ significantly by age, breed, sex, and presence/absence of neutering/spaying. The SAA concentrations were significantly higher in the diseased cat group than in the healthy cat group (p < 0.001). We observed significant increases in SAA concentrations in cats with confirmed diagnosis of inflammatory disease such as upper respiratory tract infections (p < 0.001), pneumonia (p < 0.001), pyometra (p = 0.001), and feline infectious peritonitis (p < 0.001), compared with those observed in healthy cats. Conversely, no increase was observed in cardiomyopathy, hyperthyroidism, and diabetes mellitus without systemic inflammation. In univariate analysis, survival at 30 days (p = 0.03) differed significantly between the low and high SAA concentration groups, but not at 180 days. In multivariate analysis, survival at 30 days did not significantly affect SAA concentration. Measurement of SAA concentration is a useful biomarker for detecting the presence or absence of inflammation in diseased cats. However, it may not be useful as a biomarker for determining the prognosis of the disease.